Sedimentary evidence of Late Holocene human activity in the Pearl River delta, China - Lloyd, Jeremy M. (2012)
This study examines the sedimentary evidence of human activities during the last 4000 years in the Pearl River deltaic area. The analyses are focused on indentifying agricultural signatures present in the sedimentary record and establishing the timing of a change from a simple, rice-based agriculture to a more advanced, diverse agriculture. The examination is based on modern sediment and plant samples and a sediment core collected from the deltaic area. The analyses include particle size and diatom analysis to determine the environmental conditions that were associated with the period of human activities. Organic carbon isotope ratios and major metal elements reveal an expansion in commercial crop production and metal smelting in the Pearl River delta area about 2000 years ago. The input of organic matter from introduced sugarcane, a C4 plant, elevates the bulk organic carbon isotope values in the estuarine sediments above that represented by other common agricultural crops in the study area, including rice, banana and lotus, which are all C3 plants. The increase in bulk organic isotopic value coincides with the rise in the concentration of copper, iron and lead in the sedimentary sequence, suggesting a wider use of metal tools. These results indicate that advanced agriculture started about 2000 years ago as an expansion in human population took place in the area. This record also provides sedimentary evidence that help ascertain the timing and type of human activities that are linked to subsequent land reclamation on the deltaic plain, resulting in rapid shoreline advancement in the last 2000 years.